2016
DOI: 10.1055/s-0036-1584183
|View full text |Cite
|
Sign up to set email alerts
|

Patient Factors, Donor Age, and Graft Storage Duration Affect Osteochondral Allograft Outcomes in Knees with or without Comorbidities

Abstract: Limited data exists defining preoperative variables that affect outcomes after osteochondral allograft transplantation (OAT) in the knee. In this retrospective study, we examined 75 patients who underwent OAT for large (≥2 cm) grade IV cartilage defects in the femoral condyle. Patient variables evaluated included the following: smoking, workers compensation, body mass index (BMI), pre-injury activity level, number, and the type of co-morbidities in the operated knee, lesion location and number of grafts placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
88
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 24 publications
2
88
0
1
Order By: Relevance
“…Data from our laboratory revealed that mean chondrocyte viability in SOC OCAs (n ¼ 24, storage days ranging from 16 to 21 days) obtained from 2 tissue banks and designated for transplantation into patients was only 62% (unpublished data). Clinical data from 75 patients who underwent OCA transplantation at our center for treatment of large (>2 cm 2 ) articular defects of the femoral condyle showed that graft storage of >28 days at 4 C prior to implantation was associated with a significantly and 2.6 times lower likelihood of a successful outcome (Nuelle et al 2017), which matches data from others (LaPrade et al 2009). The other major factors to alter clinical outcomes after OCA transplantation include patients' preoperative activity levels, body mass index (Nuelle et al 2017), and surgical techniques for graft creation and implantation.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Data from our laboratory revealed that mean chondrocyte viability in SOC OCAs (n ¼ 24, storage days ranging from 16 to 21 days) obtained from 2 tissue banks and designated for transplantation into patients was only 62% (unpublished data). Clinical data from 75 patients who underwent OCA transplantation at our center for treatment of large (>2 cm 2 ) articular defects of the femoral condyle showed that graft storage of >28 days at 4 C prior to implantation was associated with a significantly and 2.6 times lower likelihood of a successful outcome (Nuelle et al 2017), which matches data from others (LaPrade et al 2009). The other major factors to alter clinical outcomes after OCA transplantation include patients' preoperative activity levels, body mass index (Nuelle et al 2017), and surgical techniques for graft creation and implantation.…”
supporting
confidence: 79%
“…Clinical data from 75 patients who underwent OCA transplantation at our center for treatment of large (>2 cm 2 ) articular defects of the femoral condyle showed that graft storage of >28 days at 4 C prior to implantation was associated with a significantly and 2.6 times lower likelihood of a successful outcome (Nuelle et al 2017), which matches data from others (LaPrade et al 2009). The other major factors to alter clinical outcomes after OCA transplantation include patients' preoperative activity levels, body mass index (Nuelle et al 2017), and surgical techniques for graft creation and implantation. Therefore, our team of orthopedic clinicians and scientists designed and implemented a comparative translational research approach to address quantity, quality, and technique limitations for successful OCA transplantation in canine and human patients.…”
supporting
confidence: 79%
“…15 The effect of BMI on OCA survival is unclear and demonstrates mixed results at short to intermediate term follow-up. 19,20 In other studies, age over 50 years old, symptom duration greater than D 3 3 X X1 year have also been identified to be associated with inferior outcomes. [21][22][23] The location of the chondral defect, extent of chondral disease, and concomitant pathology may also affect the outcome of OCA.…”
Section: Allograftmentioning
confidence: 89%
“…A safe and effective surgical treatment for large (>2.5 cm 2 ) articular defects is osteochondral allograft (OCA) transplantation . Fresh OCA transplantation has been associated with 88% return to sport and greater than 75% 10‐year survival rates for treatment of large femoral condyle lesions . However, reoperation and failure rates average 30.2% and 18.2%, respectively, which suggests methods for addressing current limitations are needed.…”
mentioning
confidence: 99%
“…One of the major causes of failure for OCA transplantation is loss of essential chondrocyte viability during the preservation and storage period of tissue prior to eligible patient matching and transplantation. Essential chondrocyte viability for OCAs is considered to be at least 70% of day 0 viable chondrocyte density with successful preclinical and clinical outcomes strongly corresponding to this key metric for graft quality . While chondrocyte viability at time of OCA transplantation has been reported to be a contributing factor to successful outcomes, it is also possible that metabolic responses of the OCA in transitioning from storage temperature to body temperature may contribute to mechanisms causing failure.…”
mentioning
confidence: 99%